Formation of the interface between c-Si(111) and diamond-like carbon studied with photoelectron spectroscopy - Ristein, Jürgen; Ley, Lothar; et al. (Applied Surface Science, 1998)
The hydrogen-terminated Si(111) surface was used as a substrate to grow amorphous hydrogenated carbon (a-C:H) films by means of layer-by-layer plasma deposition. Electronic and structural properties of the forming interface were determined by in situ core level and valence band photoelectron spectroscopy. From the core level spectra the gradual formation of an initially carbon-rich and eventually stoichiometric silicon carbide interface layer is inferred with a final thickness of 18 Å. The silicon core level data indicate that the substrate is hydrogen-passivated owing to the plasma exposure. On the final heterostructure, the valence band edge of the diamond-like carbon is found to be 0.4 eV below that of the interfacial a-SiC:H and also below that of the silicon, with the offset amounting to 0.7 ± 0.1 eV. © 1998 Elsevier Science B.V.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.IAP.exphys.format
Keywords: Band bending; Band offset; Photoelectron spectroscopy; Silicon-carbon interface